Linguistische Analyse polnischer Arztbriefe – eine Pilotstudie - Jaremkiewicz-Kwiatkowska, Anna; Nycz, Krzysztof (2022)
In the pilot study, a linguistic analysis of 15 Polish hospital discharge summaries from the field of hematology / oncology, orthopedics and psychiatry / psychosomatics is conducted. The focus of this study is the linguistic style of the summaries, which results from the communicative asymmetries in the doctor-patient relationship, as well as the occurrence of metaphor concepts which serve to cope with everyday clinical life and to convey medical contexts.
Keywords: metaphor; doctor-patient communication; hospital discharge summary; medical language; language for special purposes